PENGARUH PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE GALLERY WALK TERHADAP MOTIVASI BELAJAR PAI SISWA DI SD NEGERI 04 SETIA, KECAMATAN DUA KOTO, KABUPATEN PASAMAN - Ulpa Hasiah, Iswantir M, Wedra Aprison, Salmi Wati (JURNAL PENDIDIKAN DAN KEGURUAN, 2024)
This research is motivated by the fact seen in the field that teachers are less attractive in applying learning models, then students' lack of motivation in participating in learning activities and students' lack of interest in participating in PAI learning. The type of research used in this study is a quantitative approach, the research design used in this study is using a Quasy Experiment with a Nonequivalent Control Group Design. The population in this study amounted to 44 students consisting of three classes. The sample for this study used two classes, namely class IV A as the experimental class and class IV B as the control class. The sampling technique used in this study was purposive sampling. The data analysis technique used is the normality test, homogeneity test and hypothesis testing. Based on the research results obtained t_count = 18.088, the hypothesis is accepted which states that there is a significant influence between the Gallery Walk learning model and the conventional learning model, which means HO is rejected. So it can be concluded that there is a significant influence of the Gallery Walk learning model on students' learning motivation in the Islamic Religious Education subject at SD Negeri 04 Setia, Dua Koto District, Pasaman Regency.